PEMBERDAYAAN MASYARAKAT DESA DALAM MENDUKUNG KEMANDIRIAN PERTANIAN MELALUI RUMAH BIBIT HORTIKULTURA - Sepsriyanti Kannapadang; Enos Lolang; Anastasia Baan; Esky Naya Palulun; Sandra Pandita (Indonesian Collaboration Journal of Community Services (ICJCS), 2026)
Village agricultural independence is an important factor in supporting food security and improving community welfare. However, limited access to superior seeds and a lack of knowledge in nursery techniques remain major obstacles faced by farmers at the village level. This community service activity aims to empower village communities to support agricultural independence through the construction and utilization of horticultural seed houses. This program was implemented by KKN-T students from Class 46 of the Indonesian Christian University of Toraja in Tambunan Village, North Makale District, using a participatory approach that directly involved the community, from the planning stage, through the construction of the seed house, to training in proper nursery techniques. The seed house functions as a production center for quality horticultural seeds, such as vegetables and food crops, which can be used sustainably by the community. The results of the activity showed an increase in community knowledge and skills in nursery management, as well as an increase in the availability of superior seeds independently. In addition, this program also encouraged the formation of community working groups that play a role in the sustainable management of the seed house. Thus, this activity is expected to strengthen village agricultural independence and become a model of community empowerment that can be replicated in other areas